Recording drug responses from adult Dirofilaria immitis pharyngeal and somatic muscle cells. (April 2021) - Verma, S.; Kulke, D.; McCall, J.W.; Martin, R.J.; Robertson, A.P.
Abstract: Despite being considered one of the most pathogenic helminth infections of companion animals, members of macrocyclic lactone class are the only drugs available for the prevention of heartworm disease caused by Dirofilaria immitis . Alarmingly, heartworm prevention is at risk; several studies confirm the existence of macrocyclic lactone resistance in D. immitis populations across the United States. To safeguard the long term prevention and control of this disease, the identification and development of novel anthelmintics is urgently needed. To identify novel, resistance-breaking drugs, it is highly desirable to: Unfortunately, none of the three above statements can be answered sufficiently for D. immitis and most of our hypotheses derive from surrogate species and/or in vitro studies. Therefore, the present study aims to improve our fundamental understanding of the neuromuscular system of the canine heartworm by establishing new methods allowing the investigation of body wall and pharyngeal muscle responses and their modulation by anthelmintics. We found that the pharynx of adult D. immitis responds to both ivermectin and moxidectin with EC50 s in the low micromolar range. We also demonstrate that the somatic muscle cells have robust responses to 30 μM acetylcholine, levamisole, pyrantel and nicotine. This is important preliminary data, demonstrating the feasibility of electrophysiological studies in this important parasite. Graphical abstract: Image 1 Highlights: We have developed new preparations to record drug responses from adult heartworm. These preparations allow investigation of ion-channel responses in adult parasites. Somatic muscle cell patch-clamp recordings show responses to levamisole & pyrantel. Pharyngeal current-clamp recordings show responses to ivermectin & moxidectin.